Relevance Of Eight Documents Presented By Charu Mujumdar (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper explores the relevance of the eight documents presented by Charu Mujumdar within the context of the Communist Party of India (Maoist). These documents, crafted during a period of state oppression, have had a profound impact on the party's evolution. The study employs a historical and content analysis approach to assess the historical context, content, and enduring significance of these documents. The research aims to illuminate how these documents continue to shape the Maoist movement's agenda, even in the face of changing leadership and evolving political landscapes.